Promoting Preprint Awareness and Adoption in Africa: A Need-Driven Perspective From the African Region - Ezechukwu, Oluchukwu Ifeyinwa; Ogunniyi, Tolulope; Dine , Roseline Dzekem (My University, 2024)
Introduction Over the years, preprint has grown, especially since its impact contribution during the health emergency of the COVID-19 pandemic, and is gradually drawing the interest of funders. However, the embrace of preprint varies across different regions, with the rate of acceptability and use of preprint by researchers also leading to hesitance and resistance to submit research articles to the preprint server; hence, this is attributed to the concerns surrounding the integrity and validity of preprint articles. This study assesses the awareness, adoption, and promotion of preprints in Africa. Method This study employed a descriptive cross-sectional study design carried out among African researchers. The data were collected using an online-based, semi-structured questionnaire assessing the awareness of preprint, institutional uptake, and promotion in Africa. However, the study also assesses their opinion on the promotion of preprint and its credibility in the African research community. The qualitative data was analyzed for themes using Microsoft Excel Package, and the quantitative data were analyzed for descriptive and chi-square using SPSS version 26.0. Results Among participants, 64% were aware of preprints, 40% reported institutional promotion, and 62% recognized their relevance to institutional roles. However, 53% cited limited recognition of preprints within the scientific community. Desired benefits from preprint clubs included research funding support (83%), open peer review (82%), and access to shared opportunities (79%). No significant associations were found between participants' country, research domain, education level, or institutional role and preprint awareness, or promotion or perceived role of preprint in Africa. Participants recommended educational workshops, partnerships with academic institutions, targeted online campaigns, and localized resources to enhance preprint adoption and foster an open science ecosystem across Africa. Conclusion Preprint adoption in Africa requires addressing awareness gaps, institutional recognition, and community acceptance. Collaboration efforts, including educational initiatives, partnerships, and localized outreach, are crucial to fostering an ecosystem that supports preprints and advances open science practices.
Keywords: Preprint; Assessment; Africa; Research; Scientific Papers; Publications